Trend of Women Representation in Civil Service Bureaucracy in Nepal - Bhandari, Dila Ram (Journal of Development and Administrative Studies, 2018)
Representative bureaucracy is a sign of inclusive and democratic governance. In this article, women's participation in Nepali bureaucracy is examined both qualitatively and quantitatively in light of the adoption of the reservation policy in 2007. This study aims to determine the extent to which Nepal's bureaucracy has evolved to reflect the demographics of the nation and whether it has improved in terms of citizen responsiveness after the establishment of a reservation policy. Gender-friendly practices are being implemented as the nation moves toward modernity. PSC and CBS secondary data are employed with descriptive statistics and inferential statistics (t-test and one-way ANOVA). Women’s representation has increased through participation in the civil service, but they still mostly hold junior or non-gazetted posts. Citizens’ evaluations regarding responsiveness and processes of service provision are also mixed.